(untitled) (De Musica, 2021)
If the philosophy of music, as Giovanni Piana has pointed out, can only begin by taking a step backward, not turning immediately to music itself, but starting from the experience of sound, our society, being profoundly conditioned by computer technologies, requires a further step backward. Even before the sound, it is necessary to reflect on the condition of today’s human being and on the way in which the arts are able to describe and interpret its features. In this contribution, I will try to reconstruct the main elements of a possible reading of our times in an altermodern key, by finding in the Internet environment the instrument that best synthesizes, both strictly and metaphorically speaking, the current condition of the contemporary subject.